2012
DOI: 10.4070/kcj.2012.42.2.86
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Awareness and Treatment of High Low Density Lipoprotein-Cholesterol in Korean Adults Without Coronary Heart Diseases - The Third Korea National Health and Nutrition Examination Survey, 2005 -

Abstract: Background and Objectives The purpose of this study was to estimate the prevalence, awareness and treatment of high low density lipoprotein-cholesterol (LDL-C) level in Korean adults without coronary heart disease. Subjects and Methods National representative cross-sectional surveys, data of 5248 Korean adults (2246 men and 3002 women) aged between 20 and 79 years from the Third Korea National Health and Nutrition Examination Survey (KNHANES III, 2005) was used. High LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The current cholesterol levels of the Thai population are comparable to the levels in the U.S. in 1988–1994 [23]. The level of HDL-C in the Thai population is slightly lower than that of the Korean population reported in 2006 and 2012 [9, 24]. The Korea health survey reported that the levels of TC, LDL-C, HDL-C, and triglycerides were 184.7, 114, 45.2, and 135.2 mg/dL, respectively, which were more favorable than what was found in the Thai population in the present study [9].…”
Section: Discussionmentioning
confidence: 99%
“…The current cholesterol levels of the Thai population are comparable to the levels in the U.S. in 1988–1994 [23]. The level of HDL-C in the Thai population is slightly lower than that of the Korean population reported in 2006 and 2012 [9, 24]. The Korea health survey reported that the levels of TC, LDL-C, HDL-C, and triglycerides were 184.7, 114, 45.2, and 135.2 mg/dL, respectively, which were more favorable than what was found in the Thai population in the present study [9].…”
Section: Discussionmentioning
confidence: 99%
“…Asian people exhibit the characteristic phenotype of adiposity5 and adiposity-related lipid6 or vascular traits 5. However, studies on genetic basis of these relationships have been insufficient in this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, the incidence of hypercholesterolemia and elevated LDL-cholesterol (LDL-C) levels has been increasing in parallel, without any decrease in hypertriglyceridemia or hypo-HDL-cholesterolemia [8]. Further KNHANES database has shown that approximately 10.0% of Korean adults have LDL-C levels that needed to be pharmacologically lowered, and 19.9% have LDL-C levels that needed therapeutic lifestyle modifications [9]. Consequently, dyslipidemia stands to substantially increase the cardiovascular (CV) risk in the Korean population and needs to be considered as a major health concern in the Korean setting.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Korean real-world practice has demonstrated good compliance for at least 18 months in patients who had been started with statins at the fixed doses [22]; however, the study was performed at a single institution and lacks generalizability. Moreover, the indices of metabolic syndrome in Korea have historically been TG and HDL-C [9], hence it is not possible to infer LDL-C levels in the general population from the KNHANES database [23].…”
Section: Introductionmentioning
confidence: 99%